PENGARUH EKSTRAK METHANOL Hoodia macrantha SEBAGAI PENEKAN NAFSU MAKAN TERHADAP KOORDINASI MOTORIK MENCIT JANTAN - , BRIGITTA NATASHYA ANJANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Hoodia macrantha is a widely used plant in South Africa during hunting season that works as an appetite suppressant for their p57 compound which targets directly on the hypothalamus. Lately, this substance has been used a lot as weight loss supplement and the result is widely proven. Nevertheless, there has been no evidence on its side effect on motoric coordination which is also affected by the hypothalamus. Objective : This study was conducted to know the effect of oral administration of Hoodia macrantha methanol extract on male mice motoric coordination. Methods : 24 Swiss male mice were divided into 4 groups of experiment, equally. 1 group was treated as control group and the other 3 received oral dose of Hoodia macrantha methanol extract suspense for 5,15,and 50 mg/kgBW/1 ml respectively. Assessment on motoric coordination was done using rotarod experiment tool before and after oral administration. The result of pre and post experiment was analyzed using paired t test and each group were compared using one way ANOVA test. The result was determined to be significant if p<0.05 and not significant if p>0.05. Result : The body weight observed before and after oral administration showed no significant difference (p>0.05). There was no significant effect on motoric coordination after oral administration (p>0.05). There was no significant difference between dosage variation (p>0.05). Conclusion : There was no significant effect between different oral dosage administration (5,15,and 50 mg/kgBW) of Hoodia macrantha methanol extract on male mice motoric coordination.